Effect of heat and compressive stress on the hardness of iron-based metallic grass - Mohd Haiqal Eddy (2014)
Iron-based metallic glass (MG) with composition Fe80Si7B13 was subjected to heat treatment and compression in this project. This project aims to understand and explore the correlation between heat treatment and compressive stress on Hardness Value (HV) of Iron-based MG, in order to characterize the behaviour of the material. The Iron-based MG was subjected to heat treatment initially at temperatures ranging from 300°C to 600°C, and then followed by compression and the order of the process was then switched to compare the significance of the order in relation to the behaviour of the sample. The effect of annealing time up to four hours was also studied in this experiment to investigate if varying the annealing time at a constant temperature of 300°C would result in an increase or decrease in HV. Heat treatment and compression were also simultaneously applied to the sample to investigate if crystallization would occur at a temperature lower than the crystallization temperature. It was shown that thermal annealing at temperatures lower than the crystallization temperature of the sample would result in an increase in HV due to structural relaxation phenomena which leads to reduction in free volume. In addition the low compressive stress of 278.3kPa exerted onto the sample did not result in a significant change in HV because the material does not undergo plastic deformation, but only elastic deformation. Evolution of compressive residual stress might be a factor to cause the HV of the sample to increase when a combination of thermal annealing and compressive stress was applied.